The Influence of CYP3A4 Polymorphism in Sex Steroids as a Risk Factor for Breast Cancer - Veiga, Melissa Gonzalez; Felizi, Rogério Tadeu; Reis, Dayane Guerino; Carelli Filho, Ivo; Fernandes, Cesar Eduardo; Souto, Ricardo Peres do; Oliveira, Emerson (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective Epidemiological studies have shown evidence of the effect of sex hormones in the pathogenesis of breast cancer, and have suggested a relationship of the disease with variations in genes involved in estrogen synthesis and/or metabolism. The aim of the present study was to evaluate the association between the CYP3A4*1B gene polymorphism (rs2740574) and the risk of developing breast cancer.Methods In the present case-control study, the frequency of the CYP3A4*1B gene polymorphism was determined in 148 women with breast cancer and in 245 women without the disease. The DNA of the participants was extracted from plasma samples, and the gene was amplified by polymerase chain reaction. The presence of the polymorphism was determined using restriction enzymes.Results After adjusting for confounding variables, we have found that the polymorphism was not associated with the occurrence of breast cancer (odds ratio = 1.151; 95% confidence interval: 0.714–1.856; p = 0.564). We have also found no association with the presence of hormone receptors, with human epidermal growth factor receptor 2 (HER2) overexpression, or with the rate of tumor cell proliferation.Conclusion We have not observed a relationship between the CYP3A4*1B gene polymorphism and the occurrence of breast cancer.
Keywords: Cyp3a4; breast cancer; polymorphism; estrogens; genetics